Pemetaan Potensi Atletik Siswa Sekolah Dasar: Identifikasi Bakat Tolak Peluru melalui Metode Sport Search di SD Negeri Cikiara - Cucu Hidayat; Hartadji, Rd. Herdi; Syafei, Pepep Mochamad; Rahmat, Agus Arief; Listyasari, Endah; Ucu Muhammad Afif; Aang Rohyana (Universitas Singaperbangsa Karawang, 2024)
This study aims to obtain a description of the talent of prospective athletes in the athletic sport of shot put among students of SD Negeri Cikiara Cipedes District Tasikmalaya City. This study used a descriptive exploratory method with a population of 26 grade V students, who were sampled through a total sampling technique. The instrument used in this study was to use a standardized talent scouting test in accordance with the guidelines of the Office of the Minister of Youth and Sports. The test was conducted using the Sport Search method, which includes six test items to identify students' athletic potential. The results of the analysis showed that out of 26 students, there were 15 students who were categorized as talented or gifted in the sport of shot put. Based on these findings, it can be concluded that 11-year-old students of SD Negeri Cikiara, Cipedes Subdistrict, Tasikmalaya City have a fairly good level of talent as prospective bullet throw athletes. This research provides recommendations for the development of school-based training programs to optimize students' sports potential.